ASPEK BIOLOGIS ULATSUTERA (Bombyx mori L.) DARI DUA SUMBER BIBIT DI SULAWESI SELATAN - Sitti Nuraeni; Beta Putranto (PERENNIAL, 2008)
The purpose of this research to compared the biological aspect of silkworm seeds with two resources of seeds in South Sulawesi are Perum Perhutani (P1) and China hybrid (P2). The result of this research can be information for user of the sericulture. The observation will be done the hatchability of eggs, resistance of larva, and the characteristic of the larval. The observation of the cocoon quality such as whole fresh cocoon weight, the cocoon without pupa weight, the presentation of shell cocoon, the presentation of abnormal cocoon, and the characteristic of the cocoon. The data was analyzed with using proportion different test and t-student test. The result of this research was showed that hatchability of kind eggs as not significant. The resistance of larva as the higher from P2 and presentation of abnormal cocoon was lower. So the cocoon without pupa was not significant with the seeds from P1, but the cocoon weight and size of cocoon are bigger than from P2. Both larva motif and cocoon characteristic from P1 and from China hybrid is significant, but larva stadia from P2 was shorter than from P1. Key words : Biological aspect, silkworm (Bombyx mori), seeds resources References